2019
DOI: 10.1039/c9md00272c
|View full text |Cite
|
Sign up to set email alerts
|

Developing degraders: principles and perspectives on design and chemical space

Abstract: Degraders (e.g. PROTACs, SNIPERs, degronimers etc.) are a new modality offering increasing potential both as tools for basic research and therapeutic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
128
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(134 citation statements)
references
References 48 publications
2
128
0
1
Order By: Relevance
“…To assess the degradability of CDK4/6 by further ubiquitin ligases, we thought to address the E3 ligases IAP and MDM2, both commonly hijacked for degrader design. 46 For the former ligase, ligand 5 47 (Fig. 1) was selected, which was obtained in the course of an intensive structural evaluation of different IAP- based degraders.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…To assess the degradability of CDK4/6 by further ubiquitin ligases, we thought to address the E3 ligases IAP and MDM2, both commonly hijacked for degrader design. 46 For the former ligase, ligand 5 47 (Fig. 1) was selected, which was obtained in the course of an intensive structural evaluation of different IAP- based degraders.…”
Section: Chemistrymentioning
confidence: 99%
“…50 The resulting IAP-and MDM2-based degraders 35 and 37 are depicted in Tables 3 and S5 Previous reports on principles of PROTAC design highlighted the importance of different physiochemical properties to achieve successful degradation. 46,51,52 In order to assess activity determining physicochemical properties, we calculated molecular descriptors, i.e. the molecular weight, the topological polar surface area (TPSA), the number of rotatable bonds (NRotB), as well as hydrogen bond donors (HBD) and acceptors (HBA) of all compounds (Tables S1-S4, ESI †).…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…65 Degraders recruiting IAP were named specific and nongenetic IAP-dependent protein erasers (SNIPERs). [66][67][68][69][70][71][72][73][74][75][76] Later, von Hippel-Lindau ligands used for PROTAC design were identified by the Ciulli laboratory. [77][78][79] Concurrently, it was found that the E3 cereblon (CRBN) was the molecular target of the immunomodulatory drugs (IMiDs), such as thalidomide, pomalidomide, and lenalidomide.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity and size of the organic molecules of possible interest as drugs steadily increases as medicinal chemistry addresses ever more complex biological processes while also exploiting the expanding scope of synthetic organic chemistry. [1][2][3] Cheminformatics enables the exploitation and understanding of this diversity by describing molecules as molecular fingerprints, encoding their structural characteristics as a vector. [4,5] These fingerprints can be used for fast similarity comparisons forming the basis for structure-activity relationship studies, virtual screening, and the construction of chemical space maps.…”
Section: Introductionmentioning
confidence: 99%